Review of The Edinburgh Companion to W.B. Yeats and the Arts, by Charles I. Armstrong, Adrian Paterson and Tom Walker - María Cristina Guerrero-García (Review of Irish Studies in Europe)
Review of The Edinburgh Companion to W.B. Yeats and the Arts, by Charles I. Armstrong, Adrian Paterson and Tom Walker (eds.) (Edinburgh: Edinburgh University Press, 2024), 467pp., ISBN: 9781474499668, €195 (hardcover)